Pertanggungjawaban Pidana NI Atas Pengunggahan Foto-Foto Asusila Di Mediasosial - Matthew Gladden (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
Abstract-purpose writing this journal is as a requirement for graduation and get a law degree at the Faculty of Law, University of Surabaya. Practical purpose of this study is intended to expand the horizons and repertoire of thought in the field of law, the criminal liability. The results of research addressing that, NI immoral upload photographs without the permission of AF in social media Facebook, may be subject to criminal liability under Article 27 paragraph (1) of the Law of Information and Electronic Transactions, because: Meet the fault elements, namely: existence unlawful act, in this case the NI upload and display images of nude and semi-nude AF within Facebook account, so act NI proficiency level can be expressed as an unlawful act in accordance with the provisions of Article 27 paragraph (1) of the ITE. NI AF deliberately taking photographs and sleeping naked and then uploaded to multiple Facebook accounts in order for the NI-made nude photos, semi-nude and taking a bath belonging to AF can be seen by many people. NI upload the photos in bebeberapa facebook account, so that others can access the pictures of nude and semi-nude. NI actions can be categorized as an act in violation of decency. The ability responsible, in this case and convict the NI should know that such actions are not true. NI is a person who has grown up, capable law and 49 years old. The presence of errors in the form of deliberate, NI know clearly that the actions uploading photographs of nude and semi-nude AF to multiple Facebook accounts will result in nude photographs belong to the AF will be more widespread and seen by many people. Actions undertaken showed that NI NI deliberately disseminating photographs containing nudity and violate laws and regulations that exist related pornography. There is no excuse, NI perform actions taking nude photographs of AF without a state that can provide an excuse, such as a forced power (Article 48 of the Criminal Code); or defense forced beyond the limit (Article 49 paragraph (2)); or Article 51 paragraph (2)). Keywords: Criminal Liability, Uploader Immora Picture, Based On Facebook